'It's the way that you look at it'--a cognitive neuropsychological account of SSRI action in depression. - Harmer, C; Cowen, P (2013)
The fact that selective serotonin reuptake inhibitors (SSRIs) have antidepressant effects in some patients supports the notion that serotonin plays a role in the mode of action of antidepressant drugs. However, neither the way in which serotonin may alleviate depressed mood  nor the reason why several weeks needs to elapse before the full antidepressant effect of treatment is expressed  is known. Here, we propose a neuropsychological theory of SSRI antidepressant action based on the ability of SSRIs to produce positive biases in the processing of emotional information. Both behavioural and neuroimaging studies show that SSRI administration produces positive biases in attention, appraisal and memory from the earliest stages of treatment, well before the time that clinical improvement in mood becomes apparent. We suggest that the delay in the clinical effect of SSRIs can be explained by the time needed for this positive bias in implicit emotional processing to become apparent at a subjective, conscious level. This process is likely to involve the re-learning of emotional associations in a new, more positive emotional environment. This suggests intriguing links between the effect of SSRIs to promote synaptic plasticity and neurogenesis, and their ability to remediate negative emotional biases in depressed patients.